2012
DOI: 10.1016/s1003-6326(11)61405-2
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis of strain distribution in ZK60 Mg alloy during cyclic extrusion and compression

Abstract: Finite element method (FEM) analysis was used to study the strain homogeneity in the ZK60 Mg alloy during multi-pass cyclic extrusion and compression (CEC). In order to optimize the CEC processing, the effects of process parameters on the distribution of total equivalent plastic strain were investigated. The process parameters include the friction condition, and die geometry. The results show that the strain distributions in the workpiece are inhomogeneous after CEC deformation. The strains of both ends of wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Severe plastic deformation (SPD) has been a widely used method to fabricate ultrafine grained metals and alloys, by introducing an ultralarge plastic strain into a bulk metal without any significant change in the overall dimensions [4,5]. Among the various SPD techniques, equal channel angular pressing (ECAP) and cyclic extrusion and compression (CEC) are attractive due to their characteristics of processing the relatively large bulk samples [5][6][7][8][9]. Up to now, ECAP processing has received the most attention from researchers than other SPD processes, including CEC.…”
Section: Introductionmentioning
confidence: 99%
“…Severe plastic deformation (SPD) has been a widely used method to fabricate ultrafine grained metals and alloys, by introducing an ultralarge plastic strain into a bulk metal without any significant change in the overall dimensions [4,5]. Among the various SPD techniques, equal channel angular pressing (ECAP) and cyclic extrusion and compression (CEC) are attractive due to their characteristics of processing the relatively large bulk samples [5][6][7][8][9]. Up to now, ECAP processing has received the most attention from researchers than other SPD processes, including CEC.…”
Section: Introductionmentioning
confidence: 99%
“…Rolling and forging [4] belong unequivocally to the main forming technologies used for magnesium alloys processing in practice, while severe plastic deformation (SPD) techniques have been developed for effective grain refinement (ultrafine grain materials (UFG) preparation) and mechanical properties improvement in accordance with the Hall-Petch relation [6]. Among non-conventional technologies SPD techniques, such as equal channel angular pressing (ECAP) [7][8][9][10], accumulative back extrusion (ABE) [11,12], cyclic extrusion compression (CEC) [13], twist channel angular pressing (TCAP) [14], high pressure torsion (HPT) [15] or friction stir processing (FSP) [16] can be mentioned. These methods can be combined with conventional or other (SPD) technologies as well [17].…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al [13] studied the strain distribution of the ZK60 during CEC by finite element analysis. The results showed that the strain distribution was inhomogeneous after CEC.…”
Section: Introductionmentioning
confidence: 99%